Interacting with the Reader: Politeness in Engineering Research Article Discussions - Gil-Salom, Luz; Soler-Monreal, Carmen (International Journal of English Studies, 2009)
The writer’s strategy to combine the exposition of factual information with personal judgement and interaction with the reader has been analysed in a number of studies (Hunston, 1994; Hyland, 1998a, 1998b; Latour and Woolgar, 1979; Skelton, 1997). Myers’ studies (1989, 1992) on the pragmatics of politeness in scientific articles analyse politeness strategies in regularities of scientific style that are usually explained in terms of conventions. In the context of scientific communication, the researcher performs two basic tasks: presenting a claim and contradicting former theories or beliefs. Both actions could be interpreted as impolite behaviours and constitute what Brown and Levinson (1987) call face threatening acts (FTAs). In this study we explore the presence of face-redressive politeness strategies in the discussion sections of engineering research articles. The data are drawn from a corpus of 46 discussion sections in the fields of computing, telecommunications, nanotechnology and robotics.